2021
DOI: 10.1016/j.ajogmf.2021.100468
|View full text |Cite
|
Sign up to set email alerts
|

Placental histopathology after SARS-CoV-2 infection in pregnancy: a systematic review and meta-analysis

Abstract: Objectives : To report the spectrum of placental pathology findings in pregnancies complicated by SARS-CoV-2 infection. Methods : MEDLINE, EMBASE, Google Scholar and the Web of Science databases were searched up to August 11 th , 2021. Histopathological anomalies included maternal vascular malperfusion (MVM), fetal vascular malperfusion (FVM), acute inflammatory pathology (AIP), chronic inflammatory pathology (CIP), increased perivillous fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 81 publications
6
106
2
9
Order By: Relevance
“…Whilst we identified an increase in both maternal and fetal vascular malperfusion in our systematic review of studies reported between December 2019 and July 2020 (3), Girolamo et al, reported similar findings (22), and placental hypoperfusion and inflammation were identified in a more recent systematic review and meta-analysis. Other research has identified no associated placental pathology following third trimester infection, at either the macro-or microscopic level (23), or statistically significant increases in features, such as fibrin deposition (7).…”
Section: Poor Pregnancy Outcomes and Placental Pathologysupporting
confidence: 71%
“…Whilst we identified an increase in both maternal and fetal vascular malperfusion in our systematic review of studies reported between December 2019 and July 2020 (3), Girolamo et al, reported similar findings (22), and placental hypoperfusion and inflammation were identified in a more recent systematic review and meta-analysis. Other research has identified no associated placental pathology following third trimester infection, at either the macro-or microscopic level (23), or statistically significant increases in features, such as fibrin deposition (7).…”
Section: Poor Pregnancy Outcomes and Placental Pathologysupporting
confidence: 71%
“…The findings from our systematic review showed that a large proportion of pregnancies complicated by SARS-CoV-2 infection have placental histopathological abnormalities consistent with placental inflammation and hypoperfusion, while only about 17.4% of these pregnancies showed no placental anomalies. Sub-group analyses according to the presence of maternal symptoms or high-risk pregnancy showed similar results with the large majority of placenta from women with SARS-CoV-2 infection in pregnancy [11].…”
Section: Placental Changessupporting
confidence: 55%
“…It has been shown that the COVID-19 virus enters into human cells by interacting with the angiotensinconverting-enzyme receptor and there is evidence that the concentrations of these receptors are increased in the pregnant uterus and placenta [11]. These findings have been subsequently confirmed by the increased prevalence of signs of decidual arteriopathy in the placenta of infected pregnant women, demonstrating a link between infection and impaired placental function.…”
Section: Placental Changesmentioning
confidence: 95%
“…Although stillbirth was a rare outcome overall, a COVID-19 diagnosis documented during the delivery hospitalization was associated with an increased risk for stillbirth in the United States, with a stronger association during the period of Delta variant predominance. A previous study of pregnancies complicated by SARS-CoV-2 infection identified placental histopathologic abnormalities, suggesting that placental hypoperfusion and inflammation might occur with maternal COVID-19 infection ( 5 ); these findings might, in part, explain the association between COVID-19 and stillbirth. Among deliveries with COVID-19 documented during the delivery hospitalization, certain underlying medical conditions and markers of maternal morbidity, including the need for intensive care, were associated with stillbirth.…”
Section: Discussionmentioning
confidence: 86%